Complications of Open Elbow Arthrolysis in Post-Traumatic Elbow Stiffness: A Systematic Review. - Jiangyu Cai; Wei Wang; Hede Yan; Yangbai Sun; Wei Chen; Shuai Chen; Cunyi Fan (PLoS ONE)
Objective The objective of this study was to systematically review the literature for a more comprehensive understanding of the complications of open elbow arthrolysis in patients with post-traumatic elbow stiffness and provide a reference for better prevention and treatment of them. Methods The PubMed, EMBASE, Cochrane Library, and Google Scholar databases were searched for therapeutic studies with a set of inclusion and exclusion criteria. Data were extracted from selected articles, and a statistical analysis was performed to evaluate related factors and management of the complications. Results Twenty-eight articles published between 1989 and 2013, involving 810 patients, were included. Most of the complications included in the selected articles were nerve complications, heterotopic ossification, elbow instability, infection, pin-related complications and repeat elbow contracture. The total complication rate was 24.3% ± 3.0%, and the reoperation rate was 34.0%. Furthermore, the statistical analysis revealed that preoperative range of motion (β = -0.004, P = 0.01) and proportion of female (β = 0.336, P = 0.04) were the independent factors affecting the total complication rate. Conclusions Various risk factors are related to each of the complications, and we found that patients with less preoperative ROM and a higher proportion of female gender may point to a higher total complication rate. Therefore, to further improve the overall outcomes of this procedure, more and larger prospective studies should be performed to further elucidate the effects of prophylactic interventions targeting the risk factors, thus improving the methods of prevention and treatment of complications.